WORKSHOP KREATIVITAS VISUAL DAN PELATIHAN TRANSFORMASI BISNIS UMKM MAJALENGKA: MENGGALI TREN TERBARU DENGAN DESAIN CANVA, E-COMMERCE SHOPEE, DAN TIKTOK - Syamsul Arif Billah; Ajeng Ayu Wulandari, Adi Junaedi (JOURNAL OF COMMUNITY DEDICATION, 2023)
In the rapidly evolving digital era, Micro, Small, and Medium Enterprises (MSMEs) in Majalengka face various challenges and opportunities to adapt to the dynamic market changes. The "Creative Visuals and Business Transformation Training Workshop for Majalengka MSMEs" was organized to help MSMEs explore the latest trends in graphic design and e-commerce, and utilize digital platforms such as Canva, Shopee, and TikTok. The event aimed to empower MSMEs with practical skills and innovative strategies to enhance their competitiveness and online presence. The activities included training on visual communication and digital marketing strategies, covering creative design, e- commerce, digital marketing mentoring, and updates on business trends and innovations. Through a practical and interactive approach, participants were encouraged to understand and apply graphic design concepts and e-commerce strategies effectively. The results of the "Creative Visuals and Business Transformation Training Workshop for Majalengka MSMEs" show that participants were able to use Canva to create attractive visual designs, manage and optimize online stores on Shopee, and create dynamic marketing content on TikTok. With knowledge of the latest trends and innovations, participants can adjust their marketing strategies to remain relevant and competitive in the ever-changing market. These skills help participants enhance their online presence, competitiveness, and market reach of MSMEs in the digital era.